Assessing the Possibilities and Speculations of Blended Teaching-Learning (BTL) Based on the Online Teaching-Learning (OTL) Experience during COVID-19 in Bangladesh - Chaitee, Nazmun (Technium Social Sciences Journal, 2026)
This research paper investigates the potential and viability of implementing Blended Teaching Learning (BTL) in Bangladesh, drawing on the lessons learned from the COVID-19 Online Teaching Learning (OTL) practice experiences. The study specifically focuses on examining the advantages and challenges encountered by teachers and students in online classes during the pandemic. Through a mixed-methods approach, including questionnaire surveys, interviews, and focus group discussions (FGDs), data was collected from secondary-level teachers and students in Bangladesh. The findings highlight the dedicated efforts made by educators and students in embracing and adapting to online education during the COVID-19 crisis. Furthermore, the study identifies hindering factors, such as inadequate infrastructure, limited network availability in rural areas, lack of access to devices, insufficient training and skills, and socioeconomic disparities among guardians. Despite these challenges, the research underscores the willingness of teachers and students to embrace the BTL approach in the "new normal" educational landscape. Overall, this study provides insights into the potential for implementing BTL in secondary schools in Bangladesh, highlighting both the opportunities and obstacles that need to be addressed for its successful implementation.